The diversity of banana cultivars in East Kalimantan based on morphological characteristic - Sonja Verra Tinneke Lumowa; Widi Sunaryo; Reflinur Reflinur; Dora Dayu Rahma Turista; Ruqoyyah Nasution; Yaskinul Anwar; Zenia Lutfi Kurniawati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Banana is a plant with nutritious fruit and can help prevent stunting. Banana plants are widely cultivated in East Kalimantan, but the type characterization has not been identified. The purpose of this study was to determine the diversity of banana plants in East Kalimantan and to characterize banana plants based on morphology. This research is explorative in nature by identifying directly in the field the cultivated banana cultivars. Morphological characterization of stems, leaves and fruit was carried out based on the banana description contained in IPGRI-INIBAP/CIRAD. The research instrument is a banana morphology observation sheet which contains parameters: leaf habit, pseudostem color, predominant underlying color of the pseudostem, sap color, blotches at the petiole base, blotches color, petiole canal leaf III, color of leaf upper surface, color of midrib dorsal surface, color of leaf lower surface, color of midrib ventral surface, wax on leaves. The result shows that at East Kalimantan is found 12 types of banana cultivars were found, Talas bananas, Rutai bananas, Kepok bananas, Mas bananas, Morosebo bananas, Tanduk bananas, Susu bananas, Maulin bananas, Red bananas, Ambon bananas, Raja bananas, and Cavendish bananas.There are variations in the morphological characteristics of banana plants, leaves and fruit that can characterize each banana.